2019
DOI: 10.17219/dmp/102946
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of condylar position in patients with temporomandibular disorder (TMD) and asymptomatic patients using cone-beam computed tomography

Abstract: Background. Temporomandibular disorders (TMD) are the most common reason of non-dental pain in the orofacial region. A clinical examination of the temporomandibular joint (TMJ) with additional imaging is the most recommended procedure for TMD diagnosis. Objectives. The objective of this study was to evaluate the association between TMD and the condylar position in the glenoid fossa by examining a group of patients suffering from TMD compared with a control group of patients without TMD. In this study, we used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 39 publications
2
26
0
1
Order By: Relevance
“…The authors did not find any studies in the literature investigating the relationship between condylar position and HCA. However, some studies found the posterior condylar position was associated with any TMD [18,22,28]. Cho et al [4] concluded the posterior condylar position was more common in joints with osseous changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors did not find any studies in the literature investigating the relationship between condylar position and HCA. However, some studies found the posterior condylar position was associated with any TMD [18,22,28]. Cho et al [4] concluded the posterior condylar position was more common in joints with osseous changes.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of condylar position on TMJ health is a controversial issue. The predominant opinion is that TMD patients generally have a posterior condylar position [4,18,22,28]. However, some authors have suggested no significant association between condylar position and clinical or radiological findings of TMJ [19,24].…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for the exclusion of the articles were recorded in an adjacent column and presented in the results (Table 2). [25] Quantitative data of AEI is not shown Piancino, 2020 [16] Concerning on TMDs patients with or without condylar asymmetry Sa, 2017 [26] Patients with degenerative bone diseases Rabelo, 2017 [27] No direct relationship between fossa shape and TMDs Türp, 2016 [28] No direct relationship between AEI and TMDs Su, 2014 [29] Grouping of the glenoid fossa is not cleaṙ Ilgüy, 2014 [30] The diagnosis of participates is not clear Çaglayan, 2014 [31] Same data as Sümbüllü, 2012 [3] Learreta, 2013 [32] Group divided based on alterations in the condylar axis Robinson de Senna, 2009 [33] No description of the morphology of the fossa Hirata, 2007 [34] Sample size is too small Kurita, 2006 [35] Morphological research Tanaka, 2004 [8] Dry skull study, no TMDs diagnosis Pullinger, 2001 [36] Same data as Pullinger, 2002 [19] Kurita, 2000 [37] Grouping is not clear Toyama, 1999 [38] Only the relationship between disk and fossa…”
Section: Study Selectionmentioning
confidence: 99%
“…It can be thought in line with the data in the literature that; angular differences in the mandible may transmit the masticatory force to the TMJ in different unwanted ways, and this may cause joint disease due to the formation of abnormal Angular measurements of the mandible in adults with temporomandibular joint disorders: a CBCT study forces in the joint area. [6][7][8] Studies on TMJ patients have been focused on the mandibular condyle, mandibular morphology, and morphological changes in the joint disc. [6][7][8] However, the studies on the relationship of mandibular angular differences with TMD are limited.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Studies on TMJ patients have been focused on the mandibular condyle, mandibular morphology, and morphological changes in the joint disc. [6][7][8] However, the studies on the relationship of mandibular angular differences with TMD are limited. The aim of this study, therefore, was to evaluate the relationship between mandibular angular parameters and TMD via cone-beam computed tomography (CBCT) and show whether certain angles of the mandible will differ in the TMD patients from the healthy individuals.…”
Section: Introductionmentioning
confidence: 99%